2015
DOI: 10.1007/s10646-015-1568-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine exposure impacts boldness in female Siamese fighting fish, Betta splendens

Abstract: The present study examined the effects of the selective serotonin reuptake inhibitor, fluoxetine, on the behavior of female Siamese fighting fish, Betta splendens, in three different boldness assays (Empty Tank, Novel Environment, Social Tendency). When females were unexposed to fluoxetine, boldness was consistent within a context and correlated across assays. Fluoxetine exposure affected behavior within and among individuals on multiple levels. Exposure reduced overall boldness levels, made females behave in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 53 publications
1
24
1
Order By: Relevance
“…As a result, behavioral studies have utilized the propensity of zebrafish to inspect a novel object [ 37 ] and the willingness of perch to feed in an open environment based upon perceived predation risk [ 38 ] as measures of boldness along the shy-bold continuum of animal behavioral traits [ 39 ], a key aspect of animal personality and behavioral syndromes [ 40 ]. Though this effect did not occur at concentrations under 100 μg/L in our study, this is in agreement with a recent study that found decreased boldness of fish ( Betta splendens ) exposed to fluoxetine at 0.5 and 5 μg/L for eight days compared to control fish [ 41 ]. Because our experiment compared treatment means instead of repeated measures on individuals, we cannot definitively conclude that there were changes within an individual in terms of its boldness due to chemical exposure; however, the behavioral decisions involved imply that the fish exposed to the highest fluoxetine treatment were “shyer” than control fish, on average, by engaging in less risky behavior, and potentially at the cost of reduced food intake.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, behavioral studies have utilized the propensity of zebrafish to inspect a novel object [ 37 ] and the willingness of perch to feed in an open environment based upon perceived predation risk [ 38 ] as measures of boldness along the shy-bold continuum of animal behavioral traits [ 39 ], a key aspect of animal personality and behavioral syndromes [ 40 ]. Though this effect did not occur at concentrations under 100 μg/L in our study, this is in agreement with a recent study that found decreased boldness of fish ( Betta splendens ) exposed to fluoxetine at 0.5 and 5 μg/L for eight days compared to control fish [ 41 ]. Because our experiment compared treatment means instead of repeated measures on individuals, we cannot definitively conclude that there were changes within an individual in terms of its boldness due to chemical exposure; however, the behavioral decisions involved imply that the fish exposed to the highest fluoxetine treatment were “shyer” than control fish, on average, by engaging in less risky behavior, and potentially at the cost of reduced food intake.…”
Section: Discussionsupporting
confidence: 93%
“…These assays have been used before in this species (Dzieweczynski et al, 2016) and are standard assays for examining behavioral syndromes along with some measure of aggression (for a review, see Toms et al, 2010). Assays such as the empty tank test have been used to examine depression-like behaviors in zebrafish (Cachat et al, 2010), and these behaviors change with administration of fluoxetine (Egan et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Male Siamese fighting fish have been shown to be less aggressive (Dzieweczynski and Hebert, 2012), even after as little as 3 h of exposure to 3 µg ml −1 of fluoxetine-treated water (Lynn et al, 2007), and less active (Kohlert et al, 2012) after exposure to fluoxetine via water. Given that it has recently been found that female Siamese fighting fish are less active and explore less after fluoxetine exposure (Dzieweczynski et al, 2016), we hypothesized that similar reductions in behavior would be seen in males. Reductions in activity level after acute fluoxetine exposure appear to be common in fish (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies have shown that ecologically important behavioral traits, such as activity and boldness, are affected by various emerging aquatic contaminants (Reyhanian et al, 2011;Brodin et al, 2013;Dzieweczynski et al, 2016) as well as other contaminants including inorganic mercury (Pereira et al, 2016), persistent organic pollutants (Vignet et al, 2015), and mining waste leachate (Lanctôt et al, 2016). Effects on boldness and activity have also been noted in response to ongoing large-scale changes in carbon dioxide (CO 2 ) concentrations in oceans and freshwaters (Munday et al, 2009(Munday et al, , 2010Welch et al, 2014;Regan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%